Determination of energy and protein requirements of growing guineafowl during cold season - Mandal, A B; Pathak, N N; Singh, Harpreet (The Indian Journal of Animal Sciences, 2012)
Unsexed guineafowls (397) of 3 varieties, viz. Pearl, White and Lavender, were fed 9 dietary treatments (3 energy x 3 protein levels) from 0 to 12 weeks of age in 3 growth phases (0-4, 4-8 and 8-12 weeks). Protein levels were Pâ‚, 24, 22, and 20; Pâ‚‚, 22, 20 and 18%, and Pâ‚ƒ, 20, 18 and 16% while energy concentrations in diet were Eâ‚, 12.13, 12.55 and 12.55; Eâ‚‚, 11.30, 11.72 and 11.72, and Eâ‚ƒ, 10.46, 10.88 and 10.88 MJ ME/kg for 0-4, 4-8 and 8-12 weeks of age, respectively. Live weight gain did not differ due to Eâ‚ or Eâ‚‚ levels up to 8 weeks, but during 8-12 weeks gain was higher (P